Analisis Pengaruh Store Atmosphere Terhadap Keputusan Pelanggan dalam Pemilihan Toko Bangunan: Studi Kasus pada Depo Bangunan - Dafa Nugraha; Ni Kadek Suryani; I Kadek Pranajaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of store atmosphere on customer decisions in choosing a building materials store, with a focus on the dominant elements and other factors that can strengthen or weaken this influence. The research uses a qualitative approach with a case study method at Depo Bangunan Denpasar. Data were collected through observation, in-depth interviews with employees and customers, and documentation. Informants were selected using purposive sampling from individuals who understand store atmosphere and purchasing decisions. Analysis was performed using the Miles & Huberman model, which includes data collection, reduction, presentation, and conclusion drawing. The results show that store atmosphere plays a significant role in influencing customer decisions, particularly through store layout, lighting, and supporting facilities. These elements create comfort, ease of navigation, and a positive shopping experience. However, price and customer service factors also influence purchasing decisions, which can either strengthen or weaken the impact of the store atmosphere. The implications of this study contribute to building materials retail management in designing customer-experience-based marketing strategies. Enhancements to the store atmosphere, such as rearranging the layout, providing a children's playground, and adding parking lines, can encourage customer satisfaction and loyalty. This study fills a research gap by examining store atmosphere in the context of a building materials store, which has previously been more extensively studied in the food and beverage industry.